RETELLING STORY THROUGH PICTURE SERIES TO IMPROVE STUDENTS' SPEAKING SKILL AT ASSALAM ISLAMIC JUNIOR HIGH SCHOOL NAGA BERALIH AIR TIRIS KAMPAR REGENCY - Annisa Nadya Ramadhani; Idham Syahputra (Indonesian Journal of Integrated English Language Teaching, 2022)
A spoken language is important to human life, if we would like to have a good speaking, we should have a good speaking skill. However, after observing and conducting inerview an English teacher at MTs Assalam Naga Beralih. In general, students have difficulty at retelling story through picture series, especially in speaking skill such as pronounciation, vocabulary, grammar, fluency and comprehension. The purpose of this study was to determine the significant improvement in students' speaking skills through retelling story using a series of pictures. This research used quantitative research. One Group Pre-Test Post-Test method used in this research. This research was held on October until November 2021 at MTs Assalam Naga Beralih Air Tiris Kampar Regency. The sample consisted of 25 students. Thus, speaking test was used to gather the data. The results showed that the average score of students after being taught to retell stories using a series of pictures (81.20) was higher than before being taught to retell stories using a series of pictures (63.90). Keywords: Retelling Story, Picture Series, Speaking Skills.